Romiplostim treatment allows for platelet transfusion‐free liver transplantation in pediatric thrombocytopenic patient with primary sclerosing cholangitis. (11th July 2014) - Minowa, Kei; Arai, Katsuhiro; Kasahara, Mureo; Sakamoto, Seisuke; Shimizu, Hirotaka; Nakano, Natsuko; Ito, Reiko; Obayashi, Naho; Nakazawa, Atsuko; Ishiguro, Akira
Abstract Thrombocytopenia is a major risk factor for cirrhotic liver disease. Patients with thrombocytopenia may have esophageal or gastric varices secondary to portal hypertension, leading to variceal bleeding which exposes the liver to further damage. Here, we present a female pediatric patient with PSC and CD, whose progressive thrombocytopenia was successfully controlled by romiplostim, a TPO receptor agonist. The patient developed bloody diarrhea at four yr of age, and was subsequently diagnosed with PSC and CD when seven yr old. While CD was well‐controlled by immunomodulators, the patient's thrombocytopenia gradually progressed resulting in petechiae (platelet count of 11 × 109/L) when she was 10 yr and four months old. She responded poorly to immunoglobulin and corticosteroids. Weekly subcutaneous injection of romiplostim was therefore initiated, and platelet counts were maintained over at 50 × 109/L. She was able to undergo successful LDLT without platelet transfusion seven months after the initiation of romiplostim. Romiplostim was not required after LDLT with improved platelet counts. This case report suggests that romiplostim may be effective in the treatment of thrombocytopenic children with liver cirrhosis and portal hypertension, and in eliminating the need for platelet transfusion during the peri‐transplant period.